Dementia with Lewy bodies presenting as Logopenic variant primary progressive Aphasia. Issue 5 (2nd September 2020) - Boes, Samuel; Botha, Hugo; Machulda, Mary; Lowe, Val; Graff-Radford, Jonathan; Whitwell, Jennifer L.; Utianski, Rene L.; Duffy, Joseph R.; Josephs, Keith A.
ABSTRACT: We report a patient presenting with clinical features of logopenic variant primary progressive aphasia (lvPPA) who was later diagnosed with probable dementia with Lewy bodies. LvPPA is a neurodegenerative disease that is characterized by anomia, word-finding difficulty, impaired comprehension, and phonological errors. The most common underlying pathology for lvPPA is Alzheimer's disease. However, our patient with clinical features of logopenic progressive aphasia was later diagnosed with probable dementia with Lewy bodies. This case demonstrates that lvPPA can also be an initial manifestation of a phenotype of dementia with Lewy bodies.